Exploring the level of zakat payment awareness among staff at Pejabat Agama Islam Daerah Temerloh - Abdul Moin, Nur Asyiqin (2025)
Every Muslim is obliged to fulfill the fourth pillar of Islam, which is paying zakat as it plays an important role in fostering social and economic well-being. The level of awareness regarding the importance of paying zakat among Muslims is still low even though it is a major pillar in the Islamic economic system. This is because a lack of awareness and understanding of zakat knowledge causes a few people to fail to fulfil their obligations in paying zakat as a Muslim. The aim of this study is to evaluate the level of awareness of paying zakat among PAID Temerloh staff and as well as focusing on the factors that influence a person's sensitivity in paying zakat. The study uses quantitative methodology, using Krejcie and Morgan's formula (1970) to determine the sample size from the population of 30 staff at PAID Temerloh. Data was collected using Google Form and only distributed to 28 staff who were selected as a sample. After analyzing the data, it was found that staff at PAID Temerloh have a good understanding of zakat, but their awareness of the importance of zakat knowledge remains low. The study findings show that almost all staff know about the obligation to pay zakat, but there are still gaps regarding how to implement zakat. This study concludes that zakat authorities need to further increase their efforts in promoting zakat obligations so that the amount of zakat fund collection can be increased each year.